2007
DOI: 10.3171/spi-07/11/467
|View full text |Cite|
|
Sign up to set email alerts
|

Wrong-sided and wrong-level neurosurgery: a national survey

Abstract: Object Perhaps the single greatest error that a surgeon hopes to avoid is operating at the wrong site. In this report, the authors describe the incidence and possible determinants of incorrect-site surgery (ICSS) among neurosurgeons. Methods The authors asked neurosurgeons to complete an anonymous survey. These surgeons were asked to report the number of craniotomies and lumbar and cervical discectomies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 5 publications
(1 reference statement)
0
36
0
Order By: Relevance
“…[1923] As some studies have found, almost 50% of spine surgeons report that they have performed surgery at an incorrect vertebral level during their careers. [10,11] The variable anatomy of patients has been considered a cause in up to 40% of cases. [10,11,24] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1923] As some studies have found, almost 50% of spine surgeons report that they have performed surgery at an incorrect vertebral level during their careers. [10,11] The variable anatomy of patients has been considered a cause in up to 40% of cases. [10,11,24] …”
Section: Discussionmentioning
confidence: 99%
“…[10] Nearly half of surveyed spine surgeons responded that they had performed surgery at an incorrect vertebral level during their careers. [11] Unusual patient anatomy and a failure to verify the operative site on radiography have been commonly reported. [10,11] Therefore, it is necessary to count thoracic–lumbar vertebrae preoperatively to avoid wrong-level surgery in the course of scoliosis correction due to the variation in vertebral number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These errors, which involve the intraoperative verification of the surgical patients by the surgeon after the timeout before the first incision, included faulty counting methods due to abnormal spinal anatomy, failure to use intraoperative images during the procedure, inverting the intraoperative images, and misinterpreting cloudy images without consulting radiology(18, 25, 34, 39, 4349). …”
Section: Resultsmentioning
confidence: 99%
“…In a neurosurgical study [6], ∼ 25 % of all neurosurgeons reported having performed the skin incision at the wrong level for intervertebral disk surgery. Statistics provided by the Federal Medical Society from 2008 to date include qualitative data about the type of potential medical error and the number of reported errors.…”
Section: Introductionmentioning
confidence: 99%